Clinical practice: experience with newborn screening for congenital hypothyroidism in the Republic of Macedonia - a multiethnic country - Mirjana Kocova; Violeta Anastasovska; Elena Sukarova-Angelovska; Milica Tanaskoska; Elizabeta Taseva (Springer, 2015)
To evaluate the thyroid screening program and to estimate the prevalence of congenital hypothyroidism (CH) among newborns in the Republic of Macedonia, we measured thyroid-stimulating hormone (TSH) levels in dried blood spot specimens using the DELFIA fluoroimmunoassay, over a period of 12 years. The TSH cutoff level was 10 mU/L blood. A total of 215,077 newborns were screened (94.76 %). Out of 254 recalled newborns (a recall rate of 0.15 %), 83 newborns with CH were detected, yielding a CH prevalence at screening of 1/2,591 (female to male ratio, 1.86:1). Of the CH cases, 47/107,754 (56.6 %) neonates were Macedonian, 29/70,330 (34.9 %) were Albanian, and 7/15,055 (8.4 %) were Roma. The thyroid gland was undetectable on ultrasound in 43 (51.8 %) newborns with CH, thyroid hypoplasia was confirmed in 8 (9.6 %), while 29 (34.9 %) had a normal thyroid gland. In three newborns (3.6 %), agenesis of one lobe was confirmed. Therapy with levothyroxin was initiated on average 11.7 days after birth.